Ageing of Nuclear Power Plant’s Equipment. Assessment of Reactor Pressure Vessel Ageing Effect (Global Journal of Science Frontier Research, 2023)
Ageing of materials stands for the change in their mechanical properties due to thermodynamic imbalance of the initial condition and gradually bringing the structure to equilibrium in the presence of sufficient diffusive mobility of the atoms The current paper presents the main mechanisms of degradation of the mechanical properties of the nuclear power plant equipment metal as well the models for ageing The ageing effects and ageing indicators typical for the equipment are defined The ageing process may cause loss of the appropriate functions It is important to recognize the ageing effects as well the ageing indicators Testing methods are defined for every ageing indicator The paper considers different national approaches to ageing management of structures systems and components SSCs at nuclear power plants NPPs
Keywords: nuclear power plant; ageing; assessment of ageing; long term operation